PENGARUH CURERENT RATIO (CR) DAN TOTAL ASSET TURNOVER (TATO) TERHADAP RETURN ON EQUITY (ROE) PADA PT BARITO PACIFIC Tbk PERIODE 2013-2022 - Nopa Nopiyanti; Destian Andhani (Journal of Research and Publication Innovation, 2025)
Sampling technique employed is Non-Probability Sampling. The analysis in this research utilizes the SPSS (Statistical Package for Social Sciences) software version 26.0. The research results indicate that the Current Ratio (CR) has a significant effect on Return On Equity (ROE) based on the t-test (Partial Test), where the calculated t-value is greater than the t-table value and significant at less than 0.05: (10,027 > 2,306) and significant (0,000 < 0,05). The Total Asset Turnover (TATO) does not have a significant effect on Return On Equity (ROE) based on the t-test (Partial Test), where the calculated t-value is less than the t-table value and not significant at greater than 0,05: (-1,499 < 2,306) and significant (0,172 > 0,05). The Current Ratio (CR) and Total Asset Turnover (TATO) do not influence Return On Equity (ROE) simultaneously. Based on the F-test (Simultaneous Test), it shows that the calculated F-value is greater than the F-table value and not significant at less than 0,05: (55,411 > 4,737) and significant (0,000 > 0,05). This indicates that there is no significant simultaneous influence between the Current Ratio and Total Asset Turnover on Return On Equity.